The Effect Of Classical Music Therapy On The Anxiety Of Cervical Cancer Patients With Brachytherapy In The Radiation Oncology Service Unit Of Cipto Mangunkusumo Jakarta Hospital - Nurhalimah Nurhalimah (Jurnal Kesehatan Pasak Bumi Kalimantan, 2020)
Cervical cancer is ranked seventh in the world which causes death in women from all types of cancer, while the percentage in Indonesia is estimated at 12.7% of all types of cancer. One of the therapies performed on cervical cancer patients is ionizing radiation or Brachytherapy. This action often causes anxiety with varying degrees depending on the condition and the patient's ability to manage it. This study aims to determine the effect of classical music therapy on anxiety in cervical cancer patients undergoing Brachytherapy in the radiation oncology service unit of Cipto Mangunkusumo Hospital Jakarta. This research design is Quasi Experimental, with type one group pre test and post test design with out control group. The study population was all cervical cancer patients who underwent Brachytherapy with a total sample of 42 respondents. The results showed that classical music therapy was able to reduce anxiety levels by 11.62% with a p-value of 0.000 from moderate to mild anxiety, so it can be concluded that there is an effect of classical music therapy on reducing anxiety levels in cervical cancer patients undergoing Brachytherapy. Keywords:, classical music, anxiety, cervical cancer, brachytherapy